International Legal Protection of Child Soldiers in Areas of Armed Conflict - Haikal Mubarak; Songgi Mardiansah; Manurung, Agustinus; Hadi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2024)
International legal protection of child soldiers in areas of armed conflict is a major concern on the global human rights agenda. The Convention on the Rights of the Child and the Additional Protocol on the Involvement of Children in Armed Conflict have provided an important legal framework in efforts to protect children from recruitment and use in armed conflict. However, implementation and enforcement of laws often face complex challenges, including non-compliance by parties involved in the conflict, social and economic factors, and limited legal and security institutional capacity in affected countries. Further research is needed to understand more deeply the dynamics and challenges in protecting children in areas of armed conflict and to develop more effective strategies in protecting their rights